4th URV Doctoral Workshop in Computer Science and Mathematics (Congressos, 2017)
This book of proceedings gathers the contributions presented at the 4th URV Doctoral Workshop in Computer Science and Mathematics. After the successful previous editions in 2014, 2015 and 2016 the fourth edition was held in Tarragona (Catalonia, Spain) on November 16th, 2017. It was jointly organized by the Security and Privacy research group (CRISES) and the Doctoral Program on Computer Science and Mathematics of Security of Universitat Rovira i Virgili (URV), which celebrates its 10th anniversary this year. The main aim of this workshop is to promote the dissemination of the ideas, methods and results that are developed in the Doctoral Thesis of the students of this doctorate program, and to promote the knowledge sharing, collaboration and discussion between their respective research groups.